2002
DOI: 10.1139/f02-010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of visual isolation on territory size and population density of juvenile rainbow trout (Oncorhynchus mykiss)

Abstract: Visibility is thought to affect the territory size of visually oriented animals but there have been few experimental tests of the hypothesis. We re-examined the relationship between visibility and territory size in juvenile salmonids to test the hypothesis that increasing habitat heterogeneity results in a reduction in territory size and consequently in higher population densities. Equal densities of young-of-the-year rainbow trout (Oncorhynchus mykiss) were stocked in two experimental treatments with low visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 28 publications
4
85
1
Order By: Relevance
“…Territorial enrichment with physical barriers such as kelp models and pebbles can cause fish to have smaller individual territories with less visibility of surrounding habitat (Imre et al, 2002;Höjesjö et al, 2004). We suggest that reduced visibility of territory could increase energetic costs for resident animals when they attack an intruder and, thus, fish in this situation would either decrease aggressive interactions or choose co-habitation as their best strategy.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Territorial enrichment with physical barriers such as kelp models and pebbles can cause fish to have smaller individual territories with less visibility of surrounding habitat (Imre et al, 2002;Höjesjö et al, 2004). We suggest that reduced visibility of territory could increase energetic costs for resident animals when they attack an intruder and, thus, fish in this situation would either decrease aggressive interactions or choose co-habitation as their best strategy.…”
Section: Resultsmentioning
confidence: 93%
“…We added no objects into the non-enriched tanks. These experimental conditions (enriched vs. bare tanks) were based on Imre et al (2002) and Salvanes et al (2007). Water temperature, aeration and photoperiod of experimental aquaria were similar to stoke-tank holding conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For us to move beyond 'just-so' stories speculating on the connection among environmental forces, brain and behavior, hypotheses on these connections must be specifically tested [Gould and Lewontin, 1979]. Recent papers on fishes have demonstrated experimentally that habitat complexity causes greater species diversity and richness [e.g., Lingo et al, 2006] and that limiting the visual field influences home range size, mating and feeding, showing the influence of visual stimuli on how an animal uses its space [Imre et al, 2002;Rilov et al, 2007]. Most significantly, Sol et al [2007] tested the hypothesis that big brains confer an evolutionary advantage, an assumption not tested by previous researchers.…”
Section: Increased Use Of Phylogenetically Sound Comparisons and Phylmentioning
confidence: 99%
“…Even then, our conclusion regarding the EE and aggression remains. Moreover, during our manuscript preparation and publication of our article (published in Neotropical Ichthyology Apr-Jun/ 2010 but online since Feb/2010), other reports were published that showed that EE reduces aggression or the territory size defended aggressively (leading to increased population density -cohabitation) in salmonids (Imre et al 2002;Höjesjö et al, 2004), and these reports were included in our article (Kadry & Baker, 2010). Heuts & Nijman (2011), however, arbitrarily restricted their analysis to cichlids and ignored those articles about salmonids and the article about convict cichlids (Archocentrus nigrofasciatus) by Barley & Coleman (2010).…”
Section: Letters To Editormentioning
confidence: 99%